Neuropeptide Localization in Lymnaea stagnalis: From the Central Nervous System to Subcellular Compartments - Wood, Ellen A.; Stopka, Sylwia A.; Zhang, Linwen; Mattson, Sara; Maasz, Gabor; Pirger, Zsolt; Vertes, Akos (Frontiers in Molecular Neuroscience, 2021)
Due to its relatively small number of neurons (a few tens of thousands), the well-established, multipurpose model organism Lymnaea stagnalis, the great pond snail, has been used extensively since the 1970s to study the functioning of the nervous system. Unlike the more complex brains of higher organisms, L. stagnalis has a relatively simple central nervous system (CNS) with well-defined circuits (e.g., feeding, locomotion, learning and memory) and identified individual neurons (e.g., cerebral giant cell – CGC), keys to the generation of behavioral patterns. Accumulating information from electrophysiological experiments exposes the network of neuronal connections and the neuronal circuits responsible for basic life functions. Underpinning the chemical signaling between synaptic-coupled neurons are neurotransmitters and neuropeptides. This review looks at the contributions of mass spectrometry (MS) to neuropeptide discovery and identification at different levels of CNS organization. Starting from the whole CNS, the abundances and distributions of neuropeptides in the eleven interconnected ganglia, neuronal clusters, single neurons, and subcellular compartments are captured by MS imaging and single cell analysis techniques. Combining neuropeptide expression and electrophysiological data, and aided by genomic and transcriptomic information, the molecular basis of CNS controlled biological functions is increasingly established.